Answer:
cos(θ) = -3/√10
sin(θ) = 1/√10
tan(θ) = -1/3
Explanation:
When we have a point (x, y), the angle generated between the positive x-axis and a ray that connects the origin and the point, is defined by:
cos(θ) = x/(√(x^2 + y^2))
sin(θ) = y/(√(x^2 + y^2))
tan(θ) = y/x
Now we have the point (-3, 1), then we have:
x = -3
y = 1
√(x^2 + y^2) = √((-3)^2 + 1^2) = √10
Then we just need to replace these values in the given formulas:
cos(θ) = x/(√(x^2 + y^2)) = -3/√10
sin(θ) = y/(√(x^2 + y^2)) = 1/√10
tan(θ) = y/x = 1/-3 = -1/3